Yield components and crop estimation for wheat cultivars at different sowing times - Maia Noreto, Lorena; Kreutz Rosa, Stefanie Lais; Moretti de Souza, Jorge Luiz; Klosowski, Élcio Silvério; Yuji Tsutsumi, Cláudio; de Assis Franco, Francisco (Acta Iguazu, 2020)
The objective of this study was to evaluate the yield and yield components of wheat cultivars, and compare the productivity obtained in the field and estimated with Jensen model, at different sowing dates, in Cascavel and Palotina cities, Parana state, Brazil. The experiments were carried out in the field at the COODETEC Research Center, located in Cascavel and Palotina. The experiment was conducted in a randomized blocks design in a 7 × 3 factorial, with plots consisting of six lines spaced at 5 × 0.17 meters, with seven wheat cultivars and three sowing dates, with three repetitions. The pluvial precipitation higher than crop evapotranspiration in all cultivation cycles analyzed did not prevent water deficiencies, which occurred predominantly in the heading and physiological maturation stages. The smallest water deficiencies in Cascavel (31.2 mm; April 22) and Palotina (7.2 mm; March 31), from sowing to heading, reduced grain yield by 41.7% and 42.8%, respectively, in relation to the higher productivity of each location. Small differences in yield components (NEM, NGE and MMG) provide differences in grain yield between the cultivars tested. The sowing carried out at the end of April and in May tended to have a higher yield. The best performances with Jensen model to estimate wheat grains yield were obtained for CD 1440 and QUARTZO cultivars. The Jensen model overestimated the grain yield of the CD 108, CD 1104, CD 150 and CD 154 cultivars, since the model do not consider losses due to excessive rainfall and/or pests and diseases.